Pilot study of the early start of chemotherapy after resection of primary colorectal cancer with distant metastases (Pearl Star 01) - Yoshida, Yoichiro (BioMed Central, 2013)
BACKGROUND: The start of chemotherapy usually requires a delay of about 4 weeks after surgical resection of colorectal cancer. However, there is no evidence for the required length of this delay interval. In addition, there is a chance that a patient may die because postoperative chemotherapy was not started soon enough and a metastatic tumor was able to develop rapidly. We therefore conducted a pilot study to determine the safety and feasibility of an early start of chemotherapy after the resection of colorectal cancer with distant metastases. METHODS: Five patients were enrolled. They received XELOX therapy (130 mg/m2 of oxaliplatin on day 1 plus 1,000 mg/m2 of capecitabine twice daily on days 1 to 14) on the 7th postoperative day and XELOX + bevacizumab (7.5 mg/kg of bevacizumab on day 1) after the 2nd cycle of chemotherapy. RESULTS: Five patients underwent open surgery. The procedures included right hemicolectomy in 1 patient, sigmoidectomy in 2 patients, high anterior resection in 1 patient, and Hartmann procedure in 1 patient. All patients started chemotherapy on postoperative day 7. The median number of cycles of chemotherapy was 11 (8 to 22). No postoperative complications were observed. The tumor reduction rate was 44.3% (32.0 to 66.6%). Progression-free survival was 10.3 months. CONCLUSIONS: An early start of chemotherapy after surgery is feasible and safe. These findings suggest possible changes in the start time of chemotherapy after surgery in the future. We have already started a new phase II trial to confirm the effects of the early start of chemotherapy after surgery. TRIAL REGISTRATION: UMIN000004361.